Answer:
Simplifying
6n + 7 + -2n + -14 = 5n + 1
Reorder the terms:
7 + -14 + 6n + -2n = 5n + 1
Combine like terms: 7 + -14 = -7
-7 + 6n + -2n = 5n + 1
Combine like terms: 6n + -2n = 4n
-7 + 4n = 5n + 1
Reorder the terms:
-7 + 4n = 1 + 5n
Solving
-7 + 4n = 1 + 5n
Solving for variable 'n'.
Move all terms containing n to the left, all other terms to the right.
Add '-5n' to each side of the equation.
-7 + 4n + -5n = 1 + 5n + -5n
Combine like terms: 4n + -5n = -1n
-7 + -1n = 1 + 5n + -5n
Combine like terms: 5n + -5n = 0
-7 + -1n = 1 + 0
-7 + -1n = 1
Add '7' to each side of the equation.
-7 + 7 + -1n = 1 + 7
Combine like terms: -7 + 7 = 0
0 + -1n = 1 + 7
-1n = 1 + 7
Combine like terms: 1 + 7 = 8
-1n = 8
Divide each side by '-1'.
n = -8
Simplifying
n = -8
Step-by-step explanation: